2021
DOI: 10.1684/epd.2021.1254
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients with epilepsy at high risk of cardiac death: signs, risk factors and initial management of high risk of cardiac death

Abstract: People with epilepsy have a threefold increased risk of dying prematurely, and a significant proportion is due to sudden cardiac death or acute myocardial infarctions. The causes of increased cardiovascular morbidity and mortality in epilepsy are manifold and include acute or remote effects of epileptic seizures, the longstanding epilepsy itself or antiseizure treatments. Seizurerelated cardiac arrhythmias are common and comprise bradyarrhythmia and asystole, atrial fibrillation and ventricular tachycardia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 141 publications
2
65
0
1
Order By: Relevance
“…Previous studies in apparently healthy subjects revealed an inverse correlation between PR intervals and HR, i.e., PR intervals shorten with increasing HR (9). Intriguingly, when considering the correlation between PR intervals and HR in our patients, PR interval shortening was significantly greater during left-hippocampal seizures, although absolute PR intervals and PR interval changes were within normal limits (4,9). This subtle finding is unlikely to have a clinical meaning, but may reflect a lateralized representation of the CAN with the left hemisphere being more important in the control of AV conduction.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies in apparently healthy subjects revealed an inverse correlation between PR intervals and HR, i.e., PR intervals shorten with increasing HR (9). Intriguingly, when considering the correlation between PR intervals and HR in our patients, PR interval shortening was significantly greater during left-hippocampal seizures, although absolute PR intervals and PR interval changes were within normal limits (4,9). This subtle finding is unlikely to have a clinical meaning, but may reflect a lateralized representation of the CAN with the left hemisphere being more important in the control of AV conduction.…”
Section: Discussionsupporting
confidence: 56%
“…These changes are mostly benign and may be used to detect and count epileptic seizures using wearable devices (3). Potentially lethal cardiac arrhythmias such as ventricular tachycardia or sustained asystole are rare and contribute to the elevated risk of premature mortality and sudden cardiac death in people with epilepsy (2,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ageing is associated with progressive cardiovascular pathology, which appears to be accelerated by a history of drug‐resistant seizures 20 . Certain ASMs may exacerbate SCD risk, such as those with sodium channel‐blocking effects, including carbamazepine, lamotrigine, and phenytoin 7–10 . Blockade of the cardiac sodium channels, particularly on a background of cardiovascular disease, can result in conduction abnormalities and lead to life‐threatening arrhythmias such as wide‐complex ventricular tachycardia.…”
Section: A Syndromic Approach To Establishing Clinical Criteria For Epileptic Heartmentioning
confidence: 99%
“…The epileptic heart is defined as “a heart and coronary vasculature damaged by chronic epilepsy as a result of repeated surges in catecholamines and hypoxemia leading to electrical and mechanical dysfunction, and of adverse effects of certain antiseizure medications (ASMs), which may predispose to hyperlipidemia or arrhythmias. In some patients, acquired cardiac channelopathies in response to recurrent seizures may be involved.” Although the contemporary definition of sudden unexpected death in epilepsy (SUDEP; Table 1) excludes cardiac causes, 2–5 this semantic construct should not be interpreted as ruling out the involvement of heart disease as a factor in premature sudden death in individuals with chronic epilepsy 1,6–8 . Epidemiologic studies show that the incidence of sudden cardiac death (SCD) in individuals with chronic epilepsy is threefold greater than in the general population 9–12 and is 4.5‐fold greater than SUDEP as typically defined (Figure 1).…”
Section: Introductionmentioning
confidence: 99%